Long-term low-level ambient air pollution exposure and risk of lung cancer – A pooled analysis of 7 European cohorts. (January 2021) - Hvidtfeldt, Ulla Arthur; Severi, Gianluca; Andersen, Zorana Jovanovic; Atkinson, Richard; Bauwelinck, Mariska; Bellander, Tom; Boutron-Ruault, Marie-Christine; Brandt, Jørgen; Brunekreef, Bert; Cesaroni, Giulia; Chen, Jie; Concin, Hans; et al.
Highlights: Exposure to PM2.5 was associated with higher risk of lung cancer. Elevated risks persisted even at levels lower than the EU limit value of 25 µg/m 3 . No association between NO2, BC or O3 and lung cancer incidence was observed. Abstract: Background/aim: Ambient air pollution has been associated with lung cancer, but the shape of the exposure-response function - especially at low exposure levels - is not well described. The aim of this study was to address the relationship between long-term low-level air pollution exposure and lung cancer incidence. Methods: The "Effects of Low-level Air Pollution: a Study in Europe" (ELAPSE) collaboration pools seven cohorts from across Europe. We developed hybrid models combining air pollution monitoring, land use data, satellite observations, and dispersion model estimates for nitrogen dioxide (NO2 ), fine particulate matter (PM2.5 ), black carbon (BC), and ozone (O3 ) to assign exposure to cohort participants' residential addresses in 100 m by 100 m grids. We applied stratified Cox proportional hazards models, adjusting for potential confounders (age, sex, calendar year, marital status, smoking, body mass index, employment status, and neighborhood-level socio-economic status). We fitted linear models, linear models in subsets, Shape-Constrained Health Impact Functions (SCHIF), and natural cubic spline models to assess the shape of the association between air pollution and lung cancer at concentrations below existing standards and guidelines. Results: The analyses included 307, 550 cohort participants. During a mean follow-up of 18.1 years, 3956 incident lung cancer cases occurred. Median (Q1, Q3) annual (2010) exposure levels of NO2, PM2.5, BC and O3 (warm season) were 24.2 µg/m 3 (19.5, 29.7), 15.4 µg/m 3 (12.8, 17.3), 1.6 10 −5 m −1 (1.3, 1.8), and 86.6 µg/m 3 (78.5, 92.9), respectively. We observed a higher risk for lung cancer with higher exposure to PM2.5 (HR: 1.13, 95% CI: 1.05, 1.23 per 5 µg/m 3 ). This association was robust to adjustment for other pollutants. The SCHIF, spline and subset analyses suggested a linear or supra-linear association with no evidence of a threshold. In subset analyses, risk estimates were clearly elevated for the subset of subjects with exposure below the EU limit value of 25 µg/m 3 . We did not observe associations between NO2, BC or O3 and lung cancer incidence. Conclusions: Long-term ambient PM2.5 exposure is associated with lung cancer incidence even at concentrations below current EU limit values and possibly WHO Air Quality Guidelines.